The insulin-PI3K/TOR pathway induces a HIF-dependent transcriptional response in Drosophila by promoting nuclear localization of HIF-α /Sima - Dekanty, A. (2005)
The hypoxia-inducible factor (HIF) is a heterodimeric transcription factor composed of a constitutively expressed HIF-β subunit and an oxygen-regulated HIF-α subunit. We have previously defined a hypoxia-inducible transcriptional response in Drosophila melanogaster that is homologous to the mammalian HIF-dependent response. In Drosophila, the bHLH-PAS proteins Similar (Sima) and Tango (Tgo) are the functional homologues of the mammalian HIF-α and HIF-β subunits, respectively. HIF-α/Sima is regulated by oxygen at several different levels that include protein stability and subcellular localization. We show here for the first time that insulin can activate HIF-dependent transcription, both in Drosophila S2 cells and in living Drosophila embryos. Using a pharmacological approach as well as RNA interference, we determined that the effect of insulin on HIF-dependent transcriptional induction is mediated by PI3K-AKT and TOR pathways. We demonstrate that stimulation of the transcriptional response involves upregulation of Sima protein but not sima mRNA. Finally, we have analyzed in vivo the effect of the activation of the PI3K-AKT pathway on the subcellular localization of Sima protein. Overexpression of dAKT and dPDK1 in normoxic embryos provoked a major increase in Sima nuclear localization, mimicking the effect of a hypoxic treatment. A similar increase in Sima nuclear localization was observed in dPTEN homozygous mutant embryos, confirming that activation of the PI3K-AKT pathway promotes nuclear accumulation of Sima protein. We conclude that regulation of HIF-α/Sima by the PI3K-AKT-TOR pathway is a major conserved mode of regulation of the HIF-dependent transcriptional response in Drosophila.